2000
DOI: 10.1002/1521-4141(2000)30:8<2172::aid-immu2172>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of CD30 shapes the secretion of cytokines by human γ δ T cells

Abstract: CD30 is a member of the TNF receptor superfamily, previously shown to be expressed on Hodgkin's lymphoma cells and on normal activated lymphocytes. We here show that CD30 is highly expressed on recently activated human γ δ T cells. Elevated surface levels of this molecule persisted in long‐term cultures of γ δ cells, without further cell stimulation. CD30 acted as a co‐stimulus in γ δ T cells by potentiating the intracellular Ca2+ fluxes induced by CD3 cross‐linking. The engagement of CD30 enhanced the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…CD30 is expressed and functionally costimulates secretion of Th0 cytokines and selected chemokines in peripheral V + 9/ Vˇ2 T cell lymphocytes [10]. We here show that engagement of CD30 alone is sufficient to enhance sCD30 secretion in a primary +ˇT cell clone; furthermore, CD3 activation strongly increases sCD30 release, which is further augmented by concomitant CD30 engagement, accordingly with modulation of surface CD30 expression.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…CD30 is expressed and functionally costimulates secretion of Th0 cytokines and selected chemokines in peripheral V + 9/ Vˇ2 T cell lymphocytes [10]. We here show that engagement of CD30 alone is sufficient to enhance sCD30 secretion in a primary +ˇT cell clone; furthermore, CD3 activation strongly increases sCD30 release, which is further augmented by concomitant CD30 engagement, accordingly with modulation of surface CD30 expression.…”
Section: Discussionmentioning
confidence: 63%
“…We then analyzed primary +ˇT lymphocytes, in which we have previously shown that CD30 acts as a costimulatory molecule together with anti-CD3 mAb for the release of several cytokines and chemokines [10]. +ˇT cells were stimulated with PMA and immobilized anti-CD3 mAb in the presence or absence of immobilized anti-CD30 mAb.…”
Section: Shedding Of Scd30 Is Enhanced By Triggering Of Cd30 By Agonimentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously contributed to the understanding of the TNF-R family in gd T-cell biology by demonstrating that CD30, another TNF-R family member, acts as a potent co-stimulator of chemokine and cytokine production in TCR-triggered gd T-cell clones [4]. CD30 was not only expressed on the cell surface of the gd T-cell clones, but was also released as a soluble form (sCD30) upon TCR triggering [5].…”
mentioning
confidence: 99%
“…CD30 was not only expressed on the cell surface of the gd T-cell clones, but was also released as a soluble form (sCD30) upon TCR triggering [5]. Notably, CD30 expression was particularly persistent in long-term cultured gd T-cell clones as compared with the other members of the TNF-R family that were evaluated (CD27, 41BB, CD40, TNF-R I, TNF-R II, TNF-R related protein) ( [4] and Fig. 1A).…”
mentioning
confidence: 99%